Application of the React Learning Model in Developing Students' Conceptual Understanding of Inverse Functions - Rizky Stevania Sihotang; Kurnia Putri Sepdikasari Dirgantoro (LPPM Universitas Advent Indonesia, 2024)
Conceptual understanding is the students’ skill to understand and explain the material concept based on their thinking. The researcher's finding in one of the schools in Tangerang shows the low students' conceptual understanding of grade XI on the topic Inverse Function with an average of 39%. Meanwhile, the concept in Mathematics is related to one another and becomes fundamental to solving the mathematics problem. In Mathematics, the concept is like a spiral since it's connected between the new learning and prior knowledge. Thus, the concept of understanding is really important to bridge the next material. Therefore, the solution to solve that issue is by applying the REACT learning model as contextual learning that emphasizes conceptual understanding with constructivism philosophy in each stage. The purpose of this research is to find out the application of the REACT learning model to develop students’ conceptual understanding in Grade XI in the topic Inverse Function with descriptive qualitative research. REACT learning model is started by linking the lesson with a real-world situation or students' prior knowledge (relating), then continued by finding the concept (experiencing), then applying it in solving the problem (applying), which can be done by discussing with teacher and friends (cooperating), then the students solve the Mathematics problem based on the new context for deeper understanding (transferring). By those steps, REACT learning model has been proven to develop students' concept understanding become 70% with high criteria.